(untitled) (Contexto (Universidad de los Llanos), 2024)
Within the framework of the project “Training of fish farmers from two associations on issues of water quality, feeding and fish health, in the Department of Meta”, with code 40402318, a significant training day was held for a full week, aimed at instructors of the National Learning Service (SENA), from various regions of the country, including Guajira, Huila, Putumayo, Antioquia, Cundinamarca and Meta. The training, focused on the health of aquatic organisms, took place at the SENA Hachón headquarters and at the Institute of Aquaculture and Fishing of the Llanos (IALL) during its practical phase. The main objective was to train 30 SENA instructors so that, in turn, they can replicate the knowledge acquired and strengthen the training of young apprentices in the aquaculture sector throughout the national territory.